Tractates Sotah and Nedarim - Guggenheimer, Heinrich W. (Studia Judaica, 2005)
This volume, the second of a five-volume edition of the third order of the Jerusalem Talmud, deals in part I (Soṭah) with the ordeal of the wife suspected of adultery (Num 5) and the role of Hebrew in the Jewish ritual. Part II (Nedarim) is concerned with Korban and similar expressions, vows and their consequences, and vows of women (Num 30).